Merkel cell carcinoma versus metastatic small cell primary bronchogenic carcinoma - Katya Lisette Velasquez Cantillo; Billie L. Jackson; Ana Maria Abreu Velez; Andersson Rafae; Benavides Alvarez; Michael S. Howard (Our Dermatology Online, 2013)
Merkel cell carcinoma (MCC) of the skin is a rare, aggressive, malignant neuroendocrine neoplasm. The tumor classically demonstrates positive immunohistochemistry (IHC) staining for chromogranin A(ChrA), cytokeratin 20 (CK20), neuron specific enolase (NSE) and/or achaete-acute complex-like 1 (MASH1). The newly identified Merkel cell polyomavirus (MCPyV) has been found to be associated with most MCC cases. The primary histologic differential diagnoses of cutaneous MCC is small cell primary bronchogenic carcinoma (SCLC); moreover, both are of neuroendocrine origin. SCLC accounts for approximately 10-15% of all primary lung cancer cases; this histologic subtype is a distinct entity with biological and oncological features distinct from non-small cell lung cancer (NSCLC). In contradistinction to MCC, SCLC is classically IHC positive for cytokeratin 7 (CK7) and transcription factor (TTF-1). Similar to SCLC, MCC cell lines may be classified into two different biochemical subgroups designated as Classic and Variant. In our review and case report, we aim to emphasize the importance of a multidisciplinary approach to the approach to this difficult differential diagnosis. We also aim to comment about features of the cells of origin of MCC and SCLC; to summarize the microscopic features of both tumors; and to review their respective epidemiologic, clinical, prognostic and treatment features. We want to emphasize the initial workup study of the differential diagnosis patient, including evaluating clinical lymph nodes, a clinical history of any respiratory abnormality, and chest radiogram. If a diagnosis of primary cutaneous MCC is confirmed, classic treatment includes excision of the primary tumor with wide margins, excision of a sentinel lymph node, and computed tomography, positron emission tomography and/or Fluorine-18-fluorodeoxyglucose positron emission tomography scan studies